Effect of ceramic thickness and resin cement colors on the final color of various monolithic CAD/CAM materials - Neşe Cızıroğlu; Erman Bülent Tuncer; Recep Kara (BMC Oral Health)
Abstract Purpose To assess the impact of resin cement color and the thickness of monolithic CAD/CAM materials on the final color of the fixed dental restoration. Materials and methods Four high translucent monolithic CAD-CAM materials in shade A2, including lithium disilicate glass-ceramic (IPS e.max CAD, IP), monolithic zirconia (Ceramill Zolid HT+, CZ), two zirconia-reinforced lithium silicate ceramics (VITA Suprinity, VS, and Celtra Duo, CD) were prepared as rectangular specimens measuring 12 × 14 mm in two thicknesses (0.5 mm and 1 mm), (N = 160, n = 20 per group). Subsequently, three different colors of PANAVIA™ SA(PV) Cement Universal Automix Universal (A2), White (W), and Translucent (Tr) polymerized resin cement specimens (12 × 14 × 0.2 mm) were placed underneath the ceramic samples. After and befor aging color values were measured. The color difference was calculated using CIEDE2000 formulae. Statistical analysis was conducted using a three-way ANOVA and EMF function with Bonferroni correction. Results The 3-way ANOVA for the color difference data showed a statistically significant effect of all three main factors ceramic thickness, materials, and resin cement (p < 0.05). Among these, resin cement color had the most pronounced influence on color change (ηp² = 0.974). The most significant color change was observed with a thickness of 0.5 mm and white cement, with mean ∆E values ranging from 7.72 to 3.40. All ceramic groups, except for monolithic zirconia, exhibited color changes exceeding the clinically acceptable threshold (∆E ≤ 3.5). Additionally, all ceramic groups, except for monolithic zirconia, were affected by thickness. Conclusion The study revealed that material type and cement group significantly influenced ∆E values in certain ceramics (CD, IP), while others (CZ+, VS) remained unaffected at 1 mm thickness. These findings highlight the importance of selecting appropriate cement color and type to optimize the final esthetics of monolithic restorations.